SIKAP MAHASISWA TERHADAP UNGKAPAN PELESTARIAN LINGKUNGAN DI KAMPUS KONSERVASI: KAJIAN EKOLINGUISTIK DI UNIVERSITAS NEGERI SEMARANG - Yuniawan, Tommi; Masrukhi, Masrukhi; Alamsyah, Alamsyah (Universitas Negeri Semarang, 2014)
This study aims to describe the knowledge and attitudes of students to expose conservation on campus. This implies there are phrases that are used to always uphold the principle of the protection, preservation, utilization and sustainable development of natural resources and cultural arts, the preservation of the environment on campus conservation. Alteration between environmental changes and the language learned through ekolinguistik study. Based on student attitudes toward environmental conservation can be identified expression of the most popular expressions are: âEmbung, Di Kampus: Jalan Kaki atau Bersepeda, Yuk!, Salam Konservasi, Bebas Sepeda Motor, Flora, Fauna, Sampah Organik, Sampah Anorganik, Menanam Pohon, Menanam Harapan, Konservasi Budaya, serta Ramah Lingkunganâ. In addition, this research was also identified most not popular expressions that are: Birdfeeder, Peta Tutupan Lahan, Birdwatching, Sarasehan Selasa Legen, Buletin Pelangi Konservasi, Etalase Konservasi, Kicau Konservasi, Majalah Konservasi, Green Corridor, serta Bangunan Hemat Energi. Attitudes and knowledge of students in the development of the University of Creation is one of the keys to success vision application of Unnes. This implies that student attitudes toward environmental conservation on campus will affect the behavior of students in private or community conservation.